Case reportPainful piezogenic papules – case report - Bergler-Czop, Beata; Trzmiel, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Painful piezogenic papules – numerous adipose hernias – is a rather frequent sickness. A case of painful piezogenic papules will be introduced. They were found on the feet and in the area of the wrists of an eighteen-year-old patient. At the beginning there were some difficulties with the diagnosis. On admission thanks to the physical examination numerous small, hard, diaplastic nodules of yellow colour were found at the margins of both feet, heels and on the internal area of the wrists. The changes on the feet were visible in a standing position, palpably painful, causing difficulties while walking. In laboratory examinations no significant abnormalities were found. The clinical picture and the medical history of the patient confirmed the diagnosis of painful piezogenic papules. The patient stayed under the control of the orthopaedist. The aim of this was medical use of inserts that reduce pain. Key words: painful piezogenic papules, difficulties in diagnosis.